2021
DOI: 10.3389/fnbeh.2021.632906
|View full text |Cite
|
Sign up to set email alerts
|

Social Disconnectedness, Loneliness, and Mental Health Among Adolescents in Danish High Schools: A Nationwide Cross-Sectional Study

Abstract: Background: Previous research has suggested that social disconnectedness experienced at school is linked to mental health problems, however, more research is needed to investigate (1) whether the accumulation of various types of social disconnectedness is associated with risk for mental health problems, and (2) whether loneliness is a mechanism that explains these associations.Methods: Using data from the Danish National Youth Study 2019 (UNG19), nation-wide cross-sectional data from 29,086 high school student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 88 publications
5
39
0
1
Order By: Relevance
“…School connectedness was also associated with teen depression and anxiety. These findings replicate previous research that documents the protective impact of schools on adolescent mental well-being [ 17 , 31 , 45 ]. What is noteworthy is that youth perceptions of school connectedness exerted a greater effect on teen depression above that of family poverty level and other contextual domains.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…School connectedness was also associated with teen depression and anxiety. These findings replicate previous research that documents the protective impact of schools on adolescent mental well-being [ 17 , 31 , 45 ]. What is noteworthy is that youth perceptions of school connectedness exerted a greater effect on teen depression above that of family poverty level and other contextual domains.…”
Section: Discussionsupporting
confidence: 89%
“…For example, research has shown that U.S. adolescents with an average age of 15.5 years who reported an increased sense of school connection reported less depressive symptoms including suicidal ideations and less anxiety [ 17 ]. Another study that was conducted with Danish high schoolers found that social disconnectedness at school was positively associated with depressive and anxiety symptoms, suicidal ideation, sleep disturbances, and stress, and was negatively associated with mental well-being [ 31 ]. Recent empirical findings point to the benefits of youth connections in the school environment in promoting positive mental health during adolescence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a school context, loneliness plays an important role in mediating school belongingness and subjective wellbeing (Arslan, 2021), and is higher among adolescents who feel less integrated into their school (Chipuer, 2001;Kingery & Erdley, 2007). A cross-sectional study of over 29,000 adolescents in Denmark, suggested that mental health problems among adolescents may be prevented by promoting social connectedness (thus preventing loneliness) at school (Santini et al, 2021). There is also evidence that an increased sense of school connectedness can reduce loneliness and buffer mental health among adolescents (Cavanaugh & Buehler, 2015;Benner et al, 2017).…”
Section: Mental Health and Loneliness In Schoolsmentioning
confidence: 99%
“…Loneliness juga terjadi karena tidak adanya dukungan dari orang sekitarnya seperti teman sekelas, guru ataupun lingkungan sekolah. Hal ini sejalan dengan dengan penjelasan Santini et al, (2021) bahwa remaja yang tidak mendapat dukungan dari guru maupun teman sekolah dapat merasa kesepian yang menimbulkan masalah internalizing problems seperti gejala depresi, kecemasan, stres. Hal ini terjadi karena seseorang tidak mampu membentuk hubungan dengan orang lain sehingga terjadi social connectedness atau keterputusan sosial dan muncul simtom internalizing problems.…”
Section: Diskusiunclassified